SOME EPIDEMIOLOGICAL ASPECTS ASSOCIATED WITH INFECTIONS TRANSMITTED BY IXODID TICKS IN METROPOLITAN CITY - Ya. D. Yankovskaya; T. Ya. Chernobrovkinya; M. P. Onuhova; V. N. Volodina; S. V. Burova; V. V. Nikiforov; E. V. Kardonova (Архивъ внутренней медицины)
The aim of the study is to conduct a research of patient encounters concerning tick bites and incidence rates of infections transmitted by ixodid ticks among Moscow population; to estimate data about abundance of ticks infected with human diseases in Moscow region and formulate an approach to non-specific prevention of human diseases, transmitted by ixodid ticks, taking into account the city environment. Materials and methods. We have analyzied quantitative data provided by Federal Service on Surveillance for Consumer rights protection and human well-being (period: 2013-2016) about patient encounters concerning tick bites and incidence rates of infections transmitted by ixodid ticks among Moscow population. We employed standard method of collecting and tracking Ixodid ticks abundance in the parks and parklands of Moscow using “flags” and “trackers” within vegetation. Existence of infectious agents in Ixodid ticks was identified with PCR method in the laboratory of the department of highly infectious diseases FBHI «Moscow Centre of Hygiene and Epidemiology». Results and considerations. Epidemiological situation in Moscow in 20132016 concerning infections transmitted by ixodid ticks remains stressful. According to Federal Service on Surveillance for Consumer rights protection and human well-being, Lyme disease and introduced cases of tick-borne encephalitis were registered in Moscow. In 2016, 61 parks and parklands were listed as a potential life environment for Ixodid ticks. Investigation of the cases about infectioning with Lyme disease agents in Moscow region in 2013-2016 revealed that most of the cases were registered in East and North-West districts of Moscow in «Losiniy Ostrov» and «Serebryaniy Bor» parks. Conclusion. In the megapolis environment the approach to prevent infectious diseases transmitted by ixodid tick should be multifaceted. The greatest value should lie in non-specific prevention aimed on protection against several infectious agents that might be in a tick.